The Effect Of Gamification-Based Qurfuntastic Application On Hijaiyah Letter Learning Concentration In Alpha Generation Deaf Children - Nurul Fadhilah Ramadhani; Ainatul Mardhiyah; Muhammad Luthfi Dharmawan (Yayasan Rahmat Islamiyah, 2026)
This study aims to assess the influence of gamification-based Qurfuntastic application on increasing the concentration of learning hijaiyah letters in deaf children of the Alpha Generation. This study uses a positivistic paradigm with a quasi-experimental quantitative approach with a Nonequivalent Posttest-Only Control Group Design design applied to all deaf students in SLB, which is divided into experimental and control groups. The instruments were in the form of learning concentration questionnaires and digital learning media validated by experts, while the data analysis used the Mann-Whitney test because the data distribution was abnormal. The results showed that there was a significant difference between the control group and the experimental group with a significance (p = 0.003), which confirms that Qurfuntastic is more effective than conventional learning. This influence is supported by the integration of multimedia elements, sign language representation, and gamification strategies that align with the cognitive traits and visual learning preferences of deaf students. This study concludes that the gamification-based Qurfuntastic application has an effect on increasing the concentration of learning hijaiyah letters in deaf children with Gerenrasi Alpha.